PENGEMBANGAN SISTEM INFORMASI RESERVASI PEMESANAN BAJU DASTER DENGAN FITUR REKOMENDASI PRODUK DI TOKO ALLFAZA COLLECTION - Adi Febrianto; Dede Supiyan (Journal of Research and Publication Innovation, 2025)
The rapid development of the fashion industry has influenced consumer behavior in selecting clothing products, including dresses. Allfaza Collection, a store located in Depok City, still uses a manual ordering and transaction system, requiring customers to visit the store in person to make purchases. This poses a challenge for customers outside the city or those who prefer online transactions. Additionally, the absence of a product recommendation feature makes it difficult for customers to choose products that suit their preferences. This study aims to develop a web-based reservation system for daster dress orders, incorporating a product recommendation feature to assist customers in selecting suitable products. The development method used is the Waterfall model, which consists of analysis, design, implementation, testing, and maintenance stages. Data collection was conducted through direct observation, interviews with the store owner, and customer surveys to understand their product selection preferences. The research results indicate that the developed information system successfully enhances the efficiency of daster dress order transactions at Allfaza Collection. System testing was conducted using the White Box and User Response methods, demonstrating that the system facilitates customer purchases and provides real-time inventory information. With this system, customers can easily access the product catalog, place orders, and receive product recommendations based on their preferences, thereby improving customer satisfaction and store management efficiency.